HDL-apoE content regulates the cell surface displacement of hepatic lipase - Young, Elizabeth (University of Ottawa (Canada), 2009)
Human hepatic lipase (HL) is an interfacial enzyme that must be liberated from cell surface proteoglycans to hydrolyze lipoprotein triglyceride. HDL and apolipoprotein (apo)A-1 can displace HL from cell surface proteoglycans, much like heparin. HL displacement is inhibited by HDL-apoE content. Postprandial HDL is ∼2-fold better at displacing HL than fasting HDL, but only has about half the apoE content. Enriching native HDL with triglyceride decreases HDL-apoE content and increases HL displacement. In contrast, enriching synthetic HDL with apoE significantly inhibits HL displacement. HDL from fasted female normolipidemic subjects displaces HL ∼2-fold better than HDL from male subjects. HDL from female subjects also has significantly less apoE than HDL from males. Normolipidemic females have increased circulating HDL-bound HL. Hyperlipidemia has little effect on the HL displacement ability of HDL from men, while HDL from hypercholesterolemic females exhibits impaired HL displacement. HL displacement from liver HSPG therefore appears to be linked to interlipoprotein apoE exchange. Decreased HL displacement is associated with higher HDL-apoE levels and may impact vascular triglyceride hydrolysis.
Keywords: Chemistry, Biochemistry.